Exploring the self-perceived causes of eating disorders among Chinese social media users with self-reported eating disorders - Jinbo He; Yuchen Zhang; Zhiyuan Liu; Wesley R. Barnhart; Shuqi Cui; Shi’ting Chen; Yuru Fu; Feng Ji; Jason M. Nagata; Shaojing Sun (Journal of Eating Disorders)
Abstract Background Even though robust evidence suggests the high prevalence of eating disorders (EDs) in China, EDs in China are characterized by low diagnosis rates, delayed treatment-seeking, and ineffective treatments. Given that listening to patients’ perspectives and lived experiences is crucial to improving our understanding of EDs in the Chinese context, an investigation of the perceived causes of EDs in Chinese individuals with EDs represents a key step in improving the prevention and treatment of EDs in China. Aims To explore the perceived causes of EDs based on data from a sample of Chinese social media users with self-reported EDs, with a particular focus on the Zhihu platform. Methods We extracted and analyzed data through content analysis. Eight specific causes that could be classified into two groups were coded, including individual factors (e.g., “body image and eating”) and sociocultural factors (e.g., “media and cultural ideals”). Results A total of 2079 entries regarding self-reported EDs were retained for content analysis (14.7% were anorexia nervosa, 37.6% were bulimia nervosa, and 47.7% were binge-eating disorder). More than 90% of users with self-reported EDs claimed causes belonging to individual factors, while 35–51% of users claimed sociocultural factors. “Body image and eating” (68–87%) and “psychological and emotional problems” (65–67%) were the most commonly claimed specific causes, while “traumatic life events” (13–14%), “genetics and biology” (7–13%), and “sports and health” (9–12%) were the least claimed. Chi-square independent tests showed that users with different self-reported EDs disproportionately claimed certain causes. Conclusions Using large-scale social media data, findings provide a deeper understanding of the perceived causes of EDs in the Chinese context from individuals with self-reported EDs and highlight the variations in perceived causes across different self-reported ED types.